A synthetic sialic acid analogue is recognized by influenza C virus as a receptor determinant but is resistant to the receptor-destroying enzyme. - Herrler, Georg; Groß, Hans Jürgen; Imhof, Angela; Brossmer, Reinhard; Milks, G.; Paulson, J. C. (The journal of biological chemistry, 1992)
Synthetic sialic acid analogues varying in the substitutents at position C-9 were analyzed for their ability to replace the natural receptor determinant for influenza C virus, N-acetyl-9-O-acetylneuraminic acid (Neu5,9Ac2). By incubation of erythrocytes with sialyltransferase and the CMP-activated analogues, the cell surface was modified to contain sialic acid with one of the following C-9 substituents: an azido, an amino, an acetamido, or a hexanoylamido group. Among these, only 9-acetamido-N-acetylneuraminic acid (9-acetamido-Neu5Ac) was able to function as a receptor determinant for influenza C virus as indicated by the ability of the virus to agglutinate the modified red blood cells. In contrast to the natural receptors, 9-acetamido-Neu5Ac-containing receptors were found to be resistant against the action of sialate 9-O-acetylesterase, the viral receptor-destroying enzyme. No difference in the hemolytic activity of influenza C virus was detected when analyzed with erythrocytes containing either Neu5,9Ac2 or 9-acetamido-Neu5Ac on their surface. This finding indicates that cleavage of the receptor is not required for the viral fusion activity. The sialic acid analogues should be useful for analyzing not only the importance of the receptor-destroying enzyme of influenza C virus, but also other biological processes involving sialic acid.
Gesehen am 24.06.2024
Artikel-Version: 4. Januar 2021